Biodegradation of acid dyes by an immobilized laccase: an ecotoxicological approach. Issue 12 (7th November 2018) - Gioia, Larissa; Ovsejevi, Karen; Manta, Carmen; Míguez, Diana; Menéndez, Pilar
Abstract : An efficient degradation of two azo dyes by the immobilized laccase of Trametes villosa and its ecotoxicological assessment are reported. Abstract : Synthetic dyes in watercourses resulting from industrial effluent discharges cause serious ecological impacts, besides carcinogenic and mutagenic effects on human health. Thus, it is important to develop effective methods to remove the dyes from industrial wastewaters, and also to carry out adequate toxicity studies to establish their safety. Azo dyes are the main class of industrial dyes and important environmental contaminants. We have examined the decolorization of two azo dyes (Acid Red 88 and Acid Black 172) by a native Trametes villosa laccase immobilized on thiolsulfinate-agarose as well as the effect of different redox mediators in the reactions. The method was effective for the decolorization of both dyes. The immobilization method did not affect the capacity of the biocatalyst for dye degradation. Therefore, the insoluble enzyme removed 97% of the color of AR88 and 92% of AB172 in 24 hours at 22 °C in the presence of the selected redox mediators, vanillin (0.1 mM) and violuric acid (1.0 mM), respectively. In addition, the immobilized enzyme kept 78% of its initial capacity for decolorization of AR88 after three cycles of use. The ecotoxicological evaluation of the solutions showed a great variation depending on the biological systems used. In the phytotoxicity test, the decolorization products were not toxic to plants, whereas in Daphnia magna and Microtox® bioassays an acute residual toxicity was found. The last outcome shows the importance of using a battery of bioassays to determine the remaining ecotoxicity of the treated effluents before their discharge into the aquatic environment.